2015
DOI: 10.1111/1471-0528.13360
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, course and determinants of carpal tunnel syndrome symptoms during pregnancy: a prospective study

Abstract: Objective To investigate the prevalence, severity and relation to fluid retention of self-reported pregnancy-related carpal tunnel syndrome (CTS) symptoms in a large sample of pregnant women.Design A prospective longitudinal cohort study.Setting Dutch women who became pregnant between January 2013 and January 2014 in the southeast of The Netherlands.Population or sample A total of 639 Dutch pregnant women.Methods Baseline characteristics were assessed at 12 weeks' gestation. CTS symptoms were assessed using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 24 publications
2
47
1
4
Order By: Relevance
“…The reason for a higher mean values for symptom severity and functional severity in my study could be due to the post pregnant patients [17] and diabetic patients [18].…”
Section: Discussionmentioning
confidence: 58%
“…The reason for a higher mean values for symptom severity and functional severity in my study could be due to the post pregnant patients [17] and diabetic patients [18].…”
Section: Discussionmentioning
confidence: 58%
“…Also, studies restricted to female patients reported high rates of depression with significant association with pain intensity (Fernández-delas-Peñas et al and Fernández-Muñoz et al [33,34]. Even in pregnant women, higher depression scores were noted in women with CTS [35].…”
Section: Discussionmentioning
confidence: 99%
“…Four percent of the general population, 10% of the working population and over 30% of pregnant women have CTS. 28 Risk factors for CTS include repetitive hand use, obesity, pregnancy (progressively worse in later terms), diabetes, thyroid dysfunction and other medical conditions. 28 The debilitating symptoms can lead to significant disability at work and in daily activities.…”
Section: Carpal Tunnel Syndromementioning
confidence: 99%
“…28 Risk factors for CTS include repetitive hand use, obesity, pregnancy (progressively worse in later terms), diabetes, thyroid dysfunction and other medical conditions. 28 The debilitating symptoms can lead to significant disability at work and in daily activities. CTS is diagnosed by history, physical examination, electrodiagnostic studies including nerve conduction studies and electromyography, and neuromuscular ultrasound.…”
Section: Carpal Tunnel Syndromementioning
confidence: 99%